2022
DOI: 10.1108/jfbm-10-2022-0125
|View full text |Cite
|
Sign up to set email alerts
|

Moroccan family businesses professionalization: benefits and challenges

Abstract: PurposeThe purpose of this research is to study the influence of professionalization on Moroccan family businesses and the challenges that hinder its success.Design/methodology/approachThe design is based on exploratory qualitative approach based on semi-directive interviews with 15 CEOs of unlisted Moroccan family businesses to gain a better understanding of CEOs' perceptions of management professionalization.FindingsThis research work gives rise to a result that professionalization helps family businesses co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Consequently, all authors agree in one way or another that the fundamental challenge is the implementation of mechanisms to achieve the professionalization of family or non-family employees (Habba et al, 2022). FBs, like any economic activity, have profitability as a priority;…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, all authors agree in one way or another that the fundamental challenge is the implementation of mechanisms to achieve the professionalization of family or non-family employees (Habba et al, 2022). FBs, like any economic activity, have profitability as a priority;…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…(Union et al, 2022;Keen & France, 2022;Rashid & Ratten, 2020;Rozmi et al, 2020); and there are also more specific and complex challenges in FBs which are unlocking the conservative mindset, balanced use of emotional wealth, building strong relationships, family constitution, positive approach to leadership, and implementing family governance for family transmission (Rondi et al, 2019;Rehman et al, 2023;Kandade et al, 2021;Arteaga & Menéndez-Requejo, 2017;Caspersz & Thomas, 2015;De Groot et al, 2022). Therefore, it is demonstrated that the initial challenge for performance in FB in the digital age is the defamiliarization of business under a fundamental policy in the company is the professionalization of employees (Zhong et al, 2023;Habba et al, 2022) to coincide in decisions according to reason, actions and emotion. Table 8 shows the opportunities for FBs in the digital age.…”
Section: Factors Characteristics Strengths Challenges and Opportuniti...mentioning
confidence: 99%
“…Family businesses are visible in hospitality industry in a range of activities including transport, restaurants and hotels (Getz and Carlsen, 2005;O'Shea and Duarte Alonso, 2022;Habba et al, 2022). These businesses have traditionally been less competitive compared to multinational owned hotels, and hence adapting to digitalisation and other modern management practices is a critical issue for them (Chitty et al, 2019;Santiago et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Family businesses are visible in hospitality industry in a range of activities including transport, restaurants and hotels (Getz and Carlsen, 2005; O'Shea and Duarte Alonso, 2022; Habba et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The leader and the leader's attitude play a decisive role in a company's success (Szanyi-Gyenes & Almási, 2021) When examining the attitude of company leaders, a signif.icant relationship is found between the openness of company leaders to innovation and successful corporate innovation (Ónodi & Répáczki, 2022). Organisational culture characteristics also affect the aspects of strategy, knowledge management, and organisational effectiveness (Bencsik & Juhasz, 2023), and managerial knowledge plays a crucial role in preparing for future competition and international growth (Silva, González-Loureiro & Braga, 2021), the impact of professionalisation on Moroccan family businesses and the challenges to success (Habba, Allioui & Farhane, 2023).…”
Section: Leadership and Competitivenessmentioning
confidence: 99%